EXPLORING THE ENGLISH SPEAKING DIFFICULTIES FACED BY CADETS AT BAROMBONG MARINE POLYTECHNIC - Nanang Joko; Heni Wahyuningsih (Jurnal Penelitian)
This paper reports the English speaking difficulties faced by cadets with the following research questions: 1) what are the English speaking difficulties and 2) what are the factors causing English speaking difficulties. The research was conducted at Barombong Marine Polytechnic. There were 3 cadets of the nautical department and 3 cadets of technical department in the second semester in the academic year 2020 as the subjects in this research. The researcher used class observation and interviews to collect the data. The result found there were two kinds of the English speaking difficulties, namely linguistic and nonlinguistic aspects. The linguistic aspects (lack of vocabulary, incorrect pronunciation, and lack of grammatical knowledge). While, nonlinguistic aspects or psychology aspects (anxiety, lack of confidence, lack of motivation, fear of making mistake). They were categories as internal factors (anxiety, lack of confidence, lack of motivation, fear of making mistake) and external factors (environmental factors and ineffective teaching strategy).